THE EFFECTIVENESS OF BIOSYNTHESIZED ZnO NANOPARTICLES AS ANTIBACTERIALS: A LITERATURE REVIEW - Nopriyanti, Selly; Mulyani, Yani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
One of the human infections caused by bacteria is digestive tract infection, some of these bacteria include S.typhi, E.coli, S.dysenteriae. Antibiotics are required to treat infectious diseases caused by microbes; however, most antibiotics cause resistance to these microbes. To avoid this, researchers are interested in developing plant-derived antibiotics. This review aims to evaluate the antibacterial effectiveness of ZnO nanoparticles synthesized from plant extracts or microorganisms and their antibacterial activity against gram-positive bacteria (B. Cereus & S. Aureus) and gram-negative bacteria (E. Coli, K. Pneumonia & S. Thypi).  From this review, it can be concluded that ZnO nanoparticles have significant antibacterial activity against gram-negative bacteria. This antibacterial effectiveness is influenced by the particle size, ZnO-NPs concentration, and environmental conditions, such as pH and temperature. However, further studies are needed to determine the effectiveness of biosynthesized ZnO nanoparticles and their activities other than antibacterials. Keywords: Zinc Oxide Nanoparticles, Nanoparticles, Antibacterial, Biosynthesis, Green Synthesi